ARTISTIC TEXT AS AN OBJECT OF LINGUISTIC AND METHODOLOGICAL ANALYSIS - Stepanyan Albina Anatolyevna (International Journal of Literature and Language Studies, 2026)
This article is dedicated to the linguostylistic and methodological potential of literary texts in teaching French. The study aims to explore the possibilities of using literature as a multifunctional didactic resource.